PENGARUH FAKTOR EKSTERNAL DAN FAKTOR INTERNAL TERHADAP IMPULSE BUYING STUDI KASUS DI ALFAMART CITARUM RAYA SEMARANG - Kusumawardani, Ovi; Aqmala, Diana (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
Globalization is a process of economic activity and trade, where countriesaround the world into a single market forces increasingly integrated with theterritorial limits of the country without hindrance. Developments in this eraof globalization impact to human life. Based on these conditions, affect theappearance of many engaged in the retail trade of daily consumer goods invarious cities in Indonesia. This study aims to analyze the effect of Display,Positive Emotion and Store Atmosphere toImpulse Buying.This study used accidental sampling method on the visitor AlfamartCitarum Raya Semarang. Data obtained by distributing 100 questionnairesto the visitors Alfamart Citarum Raya Semarang. The independent variablein this study is the Display of Positive Emotion and Atmosphere Store whilethe dependent variableis the Impulse Buying. The statistical methods used inthis study is the Multiple Linear Regression AnalysisThe results oft his study indicate that the variable Display and PositiveEmotion there is a significant effect on Impulse Buiyng. As for theAtmosphere Store variables showed no significant effect on Impulse Buying.The results of this study also showed that the value of R Square of 21.6%while the remaining 78.4% is explained by other variables that are notproposed in this study.